One-step carboxylation reaction of saturated hydrocarbons with CO by Co(OAc) 2 catalyst under mild conditions - Asadullah, M.; Taniguchi, Y.; Kitamura, T.; Fujiwara, Y. (Applied catalysis. A, General, 2000)
Direct carboxylation reaction of saturated hydrocarbons with carbon monoxide to afford the corresponding carboxylic acids has been investigated in the presence of cobalt catalysts such as Co(OAc) 2 and K 2S 2O 8 in CF 3COOH (TFA). Alkyl trifluoroacetates were also formed in this reaction in different quantities, depending on the reaction conditions. Methane and ethane gave very low yields of the corresponding carboxylic acids only. The conversion of propane is about 89.5% (based on propane) when 1 bar (0.76 mmol) of propane reacted with 30 bar of carbon monoxide in the presence of 0.1 mmol of Co(OAc) 2 and 10 mmol of K 2S 2O 8 in 5 ml of TFA at 70°C for 15 h. In this reaction, iso-butyric acid is the major product and n-butyric acid and iso-propyl trifluoroacetate are the by-products. The maximum selectivity of iso-butyric acid obtained in this reaction is 62%. Cyclopentane and cyclohexane underwent this reaction under the same reaction conditions; the carboxylated product of cyclopentane is the minor product but, in the case of cyclohexane the carboxylated product is the major one. On the other hand, cycloheptane did not undergo the carboxylation reaction. The activation energies of the reaction of propane (7 bar) with carbon monoxide (30 bar) in the presence of Co(OAc) 2 (0.1 mmol), K 2S 2O 8(10 mmol) and TFA (5 ml) for 3 h at the temperature range of 65–80°C have been determined to be 9.7, 13.4 and 20.3 kcal/mol for the formation of iso- and n-butyric acids and iso-propyl trifluoroacetate, respectively.